FRI0447 FIRST COMPREHENSIVE LONG-TERM ASSESSMENT OF MUSCULOSKELETAL CONSEQUENCES AMONG EBOLA SURVIVORS. (2nd June 2020) - Pers, Y. M.; Dubois, A.; Barry, T. A.; Sall, M. D.; March, L.; Sow, M. S.; Keita, A. K.; Taverne, B.; Etard, J. F.; Toure, A.; Barry, M.; Delaporte, E.
Abstract : Background: The tremendous size of the 2013-2016 West African outbreak of Ebola virus disease (EVD) resulted in a sizeable population of survivors, many reporting short-term sequelae such as arthralgia and myalgia. Objectives: We aimed to report a detailed and long-term description of patients' musculoskeletal (MS) symptoms. Methods: We performed a cross-sectional study following systematic rheumatological screening of patients included in the Postebogui cohort (Conakry district). We used regression models to establish the magnitude of EVD as a risk factor for developing chronic MS pain by comparison with a control cohort and to establish risk factors for developing MS pain among survivors. Results: The study included 313 patients (55.6% female), with a median age of 28.2 years (IQR 21-37), and a median time from ETC discharge to rheumatological visit of 26.2 months (IQR 23-30). Chronic MS pain was reported in 216 (69%) patients, and was predominantly mechanical (48%). Enthesis and painful peripheral joints were largely involved (91%) with symmetrical distribution. Previous Ebola infection was a major risk factor for chronic MS pain (aOR, 6.662 [95% CI, 4.522–9.921]). Among survivors, increasing age (OR 1.14, 95% CI 1.08-1.22) and female gender (OR 3.58, 95% CI 1.22-11.80) were both associated with persistent MS pain, while myalgia experienced during the acute phase of EVD appeared protective (OR 0.14, 95% CI 0.04-0.42). Conclusion: Our study provides the most accurate long-term description of MS disorders among Ebola survivors. Joint and muscle pain sequelae are frequent and require specialized care. Disclosure of Interests: None declared